A previously unrecognized 22q13.2 microdeletion syndrome that encompasses TCF20 and TNFRSF13C. Issue 12 (14th September 2018) - Upadia, Jariya; Gonzales, Patrick R.; Atkinson, T. Prescott; Schroeder, Harry W.; Robin, Nathaniel H.; Rudy, Natasha L.; Mikhail, Fady M.
Abstract : Phelan‐McDermid syndrome (PMS, OMIM 606232) is a heterozygous contiguous gene microdeletion syndrome occurring at the distal region of chromosome 22q13. This deletion encompasses the SHANK3 gene at 22q13.33, which is thought to be the critical gene for the neurodevelopmental features seen in this syndrome. PMS is typically characterized by intellectual disability, autism spectrum disorder, absent to severely delayed speech, neonatal hypotonia, and dysmorphic features. Two patients presenting with classic clinical features of PMS have been reported to have interstitial microdeletions in the 22q13.2 region that map proximal to the SHANK3 gene (0.54 and 0.72 Mb, respectively). Here, we describe a 13‐month‐old girl with a de novo 1.16 Mb interstitial deletion in the 22q13.2 region who presented with global developmental delay, subtle dysmorphic features, and immunodeficiency. This deletion overlaps with the two previously published cases and five cases from the DECIPHER database. All eight patients share features common to patients with PMS including developmental delay and language delay, which suggests that this represents a previously unrecognized microdeletion syndrome in the 22q13.2 region. Our patient's deletion encompasses the TCF20 and TNFRSF13C genes, which are thought to play causative roles in the patient's neurodevelopmental and immunological features, respectively.